2005
DOI: 10.1007/s00595-005-3090-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Extrathyroid Extension Does Not Affect the Relapse-Free Survival of Patients with Papillary Thyroid Carcinoma Measuring 4 cm or Less over the Age of 45 Years

Abstract: These findings suggest that tumors with minimal extension should be classified to have the same T grade as those without such extension, and upstaging of such tumors is therefore not appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 6 publications
3
61
2
1
Order By: Relevance
“…In this series, Grade 1 patients had significantly worse DFS than Grade 0 patients and Grade 1 independently affected DFS on multivariate analysis, which was somewhat discrepant with our previous findings [5,9,10]. This is possibly because the patient series analyzed in this study is larger and average follow-up period is longer than those in the previous studies.…”
Section: Relationship Of Extension Grades To Patient Prognosiscontrasting
confidence: 99%
“…In this series, Grade 1 patients had significantly worse DFS than Grade 0 patients and Grade 1 independently affected DFS on multivariate analysis, which was somewhat discrepant with our previous findings [5,9,10]. This is possibly because the patient series analyzed in this study is larger and average follow-up period is longer than those in the previous studies.…”
Section: Relationship Of Extension Grades To Patient Prognosiscontrasting
confidence: 99%
“…Some investigators advocate EXT in tumors with extracapsular extension (Philips et al 1993) (T4 in AJCC 5th edition) and LN metastasis . The differentiation of extrathyroidal extension into minimal (T3b) and extensive involvement (T4) carries a prognostic implication (Ito et al 2006). We found that in patients with T3b category with negative or close margins, RAI gave a good rate of local control.…”
Section: Indications Of Ext In Ptcmentioning
confidence: 75%
“…Among them, extrathyroid extension is prominent. Several studies demonstrated that PTC patients with extrathyroid extension show a significantly poorer prognosis than those without extrathyroid extension, and they were therefore classified as being at high risk [1][2][3][4][5].The recurrent laryngeal nerve (RN) is one of the most common organs to which PTC extends. The RN can be preserved when carcinoma extension is partial and the preoperative vocal cord function is normal [6].…”
mentioning
confidence: 99%
“…Among them, extrathyroid extension is prominent. Several studies demonstrated that PTC patients with extrathyroid extension show a significantly poorer prognosis than those without extrathyroid extension, and they were therefore classified as being at high risk [1][2][3][4][5].…”
mentioning
confidence: 99%